'Nurture the sprouting bud; do not uproot it'. Using saving groups to save for maternal and newborn health: lessons from rural Eastern Uganda. (1st August 2017) - Ekirapa-Kiracho, Elizabeth; Paina, Ligia; Muhumuza Kananura, Rornald; Mutebi, Aloysius; Jane, Pacuto; Tumuhairwe, Juliet; Tetui, Moses; Kiwanuka, Suzanne N
ABSTRACT: Background : Saving groups are increasingly being used to save in many developing countries. However, there is limited literature about how they can be exploited to improve maternal and newborn health. Objectives : This paper describes saving practices, factors that encourage and constrain saving with saving groups, and lessons learnt while supporting communities to save through saving groups. Methods : This qualitative study was done in three districts in Eastern Uganda. Saving groups were identified and provided with support to enhance members' access to maternal and newborn health. Fifteen focus group discussions (FGDs) and 18 key informant interviews (KIIs) were conducted to elicit members' views about saving practices. Document review was undertaken to identify key lessons for supporting saving groups. Qualitative data are presented thematically. Results : Awareness of the importance of saving, safe custody of money saved, flexible saving arrangements and easy access to loans for personal needs including transport during obstetric emergencies increased willingness to save with saving groups. Saving groups therefore provided a safety net for the poor during emergencies. Poor management of saving groups and detrimental economic practices like gambling constrained saving. Efficient running of saving groups requires that they have a clear management structure, which is legally registered with relevant authorities and that it is governed by a constitution. Conclusions : Saving groups were considered a useful form of saving that enabled easy acess to cash for birth preparedness and transportation during emergencies. They are like 'a sprouting bud that needs to be nurtured rather than uprooted', as they appear to have the potential to act as a safety net for poor communities that have no health insurance. Local governments should therefore strengthen the management capacity of saving groups so as to ensure their efficient running through partnerships with non-governmental organizations that can provide support to such groups.